Reframing Reproductive Health: Awareness of Female Students at King Saud bin Abdulaziz University for Health Sciences Toward Polycystic Ovary Syndrome. - Abdelrahman, Walaa M.; Abouelfettoh, Amel M.; Nabil Aboushady, Reda M.; Alomar, Munira Omar; Mobaraki, Maryam Mohammed; Almejna, Wajd Abdulaziz; Aljamaan, Shahad Ibrahim; Borashaid, Rawan Rashed; Alnahdi, Amal Khalid; Alolaiwi, Fatima Wasel; Altanam, Leen Abdulmonem; Mahimaidoss, Hannah Devapriya; et al. (Nursing Forum, 2026)
Background: Polycystic ovary syndrome (PCOS) is a common hormonal disorder among women of reproductive age that can affect reproductive, physical, and psychological health. Limited awareness may delay diagnosis and management, making early recognition essential. Aim: This study aimed to assess the knowledge and attitudes of female students at King Saud bin Abdulaziz University for Health Sciences (KSAU‐HS) toward PCOS. Methods: A cross‐sectional descriptive study was conducted among 243 purposively sampled female students from different health sciences programs. Three tools were used: (1) structured interview questionnaire, (2) PCOS knowledge questionnaire, and (3) attitude Likert scale toward PCOS. Results: The mean age of students was 19.65 ± 1.32 years; 58.5% of student's demonstrated moderate knowledge of PCOS (mean score 34.04 ± 4.60); 52.4% exhibited a positive attitude toward PCOS (mean score 27.46 ± 4.24). A highly significant association was observed between knowledge and attitude levels (p < 0.001). Conclusion: The study concluded that most students had moderate knowledge and positive attitudes toward PCOS. A highly statistically significant relationship was found between knowledge and attitude levels. Recommendation: Implement targeted health education programs to increase awareness and promote proactive management of PCOS among female students.